TAL - a source of bacterial endotoxin detector in liquid biological samples - John, Akbar; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal; Kassim, Zaleha (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Endotoxins (chemically known as Lipopolysaccharide) from gram-negative microorganisms initiates clot formation in blood when it is accidentally encountered by horseshoe crab blood stream. This property was extensively studied by various researchers as a result Limulus Amebocyte Lysate (LAL) test was established. The LAL tests in general, 3 to 300 times more sensitive than the United States Pharmacopeial (USP) rabbit pyrogen test method. It is apparent that major differences among the LAL preparations lie in the area of sensitivity. Differences, up to 100-fold, exist in the sensitivity of the various LAL preparations to the same endotoxin. Based on the above perspective, a portable Kit (Endo sensor) was developed to detect the presence of bacterial endotoxin in liquid biological samples using Tachypleus Amebocyte Lysate (TAL) as a source. Sensitivity of the Kit was determined using various concentrations of prepared endotoxin standards and pyrogen free water samples. It was observed that Endo sensor could detect up to nano gram level of endotoxin in liquid biological samples which could be expressed in (EU/ml) and the labeled sensitivity of the lysated product was 0.125 EU/ ml. The gel clotting principle method was utilized for the detection of bacterial endotoxin in liquid biological samples.